Efficacy of Whole-Body versus Lesional Application of Permethrin Cream for Scabies Treatment: A Quasi-Experimental Study - Sungkar, Saleha; Haswinzky, Rose A.; Dwinastiti, Yasmine A.; Wardhana, Aji W.; Irmawati, Fanny P.; Kekalih, Aria; Widaty, Sandra (Journal of Drug Delivery and Therapeutics, 2021)
Objective: The study aims to evaluate the efficacy of whole-body versus lesional application of 5% permethrin cream for scabies eradication. Design: This quasi-experimental study was conducted on September-October 2018 at boarding schools in Bogor and East Jakarta, Indonesia. Subjects were randomized into two groups, 51 students each. Interventions: The first group received a whole-body application while the second group received lesional application of 5% permethrin cream. Evaluation was performed after 7 and 28 days. Main outcome measures: Proportion of lesions cured following the intervention Results: The prevalence of scabies was 41% and 33% at the boarding schools in Bogor and East Jakarta, respectively. Subjects from both groups had similar lesion distributions at baseline (p>0.05). Following intervention, the number of lesions reduced significantly (p<0.001) and both treatments were equally effective in treating scabies with 84.6% vs 91.5% cure rate [Relative Risk (RR) 1.8(0.6-5.0); p>0.05]. Conclusion: Lesional application of 5% permethrin is proven to be equally effective in treating scabies with higher cure rate. This method shows advantage for scabies treatment. In addition to reduce the unwanted side effects, it is more cost-effective and convenient. Further studies with larger sample size and randomized controlled trial design are warranted. Keywords: scabies, permethrin, whole-body application, lesional application, cure rate